2021
DOI: 10.1016/j.clinimag.2020.11.013
|View full text |Cite
|
Sign up to set email alerts
|

Hydrodissection - Practical applications in ultrasound-guided breast interventions

Abstract: This is a PDF file of an article that has undergone enhancements after acceptance, such as the addition of a cover page and metadata, and formatting for readability, but it is not yet the definitive version of record. This version will undergo additional copyediting, typesetting and review before it is published in its final form, but we are providing this version to give early visibility of the article. Please note that, during the production process, errors may be discovered which could affect the content, a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 18 publications
0
3
0
Order By: Relevance
“…This technique does not improve structure identification but it does help to keep structures out of the way and thus protects them from damage. 22 Thus, technique modifications introduced during the study and suggested here may completely prevent iatrogenic damage in vivo. Future studies are required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
See 1 more Smart Citation
“…This technique does not improve structure identification but it does help to keep structures out of the way and thus protects them from damage. 22 Thus, technique modifications introduced during the study and suggested here may completely prevent iatrogenic damage in vivo. Future studies are required to validate this hypothesis.…”
Section: Discussionmentioning
confidence: 93%
“…The authors believe that hydrodissection would be beneficial in vivo but ex vivo was not used as the lateral neurovascular bundle could not be accurately identified with ultrasound. This technique does not improve structure identification but it does help to keep structures out of the way and thus protects them from damage 22 . Thus, technique modifications introduced during the study and suggested here may completely prevent iatrogenic damage in vivo.…”
Section: Discussionmentioning
confidence: 98%
“…Hydrodissection is a minimally invasive procedure that involves injecting liquid into an anatomical space to facilitate dissection during surgery [ 7 ]. The use of this technique in many surgical specialties, such as thoracic surgery [ 8 ], cardiac surgery [ 9 , 10 ], urology [ 11 ], orthopedics [ 12 ], general surgery [ 13 , 14 ], otorhinolaryngology [ 15 ], and ophthalmology [ 16 , 17 ], has been reported.…”
Section: Introductionmentioning
confidence: 99%